A sustainable working life for all ages – The swAge-model. (July 2020) - Nilsson, Kerstin
Abstract: Background: Due to the demographic challenge in most countries it is important to consider making work life sustainable. A sustainable work life is of importance in all age groups when working life will be extended to a higher age. Aim: Towards a theoretical model with an impact on a sustainable working life for all ages, the swAge - model. Method: The theoretical model, the swAge-model, is developed based on grounded theory using qualitative studies, quantitative studies, intervention projects and literature reviews. Result: The swAge-model states the interactions between different ageing concepts; chronological, mental, biological and social ageing, and the nine areas of importance for individuals' work life participation. The model also states the four consideration areas whether individuals can and want to participate in an extended working life or not. The model also includes proposed measures at the organisation/enterprise level and at the society level based on the four activity areas at the individual level. Conclusion: The theoretical swAge-model describes how to reflect on working life and presents tools to extend work life in a sustainable way for older workers in modern society. The swAge-models' analysis and measure matrix is included as appendix 1. In the Nordic countries the theoretical model is use in the critical debate and as a tool for managers and authorities to make the working life sustainable for all ages. Highlights: The swAge-model describe the complexity of work life participation. Different aging concepts need to be considered in relation to societies delay of the retirement age. There are nine determinate areas for work life participation, sorted in four determinant spheres for individuals' considerations to work life participation. Those four determinant spheres are the foundation for organisational and society measures. swAge is used as a tool of governments, authorities, managers, occupational health care, HR.